2021
DOI: 10.3390/membranes11100792
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Polyelectrolyte Membranes of Pectin Graft-Copolymers with PVA and Their Composites with Phosphomolybdic Acid for Drug Delivery, Toxic Metal Ion Removal, and Fuel Cell Applications

Abstract: In this study, a simple method for the fabrication of highly diffusive, adsorptive and conductive eco-friendly polyelectrolyte membranes (PEMs) with sulfonate functionalized pectin and poly(vinyl alcohol)(PVA) was established. The graft-copolymers were synthesized by employing the use of potassium persulfate as a free radical initiator from pectin (PC), a carbohydrate polymer with 2-acrylamido-2-methyl-1-propanesulphonic acid (AMPS) and sodium 4-vinylbenzene sulphonate (SVBS). The PEMs were fabricated from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 53 publications
(56 reference statements)
0
4
0
Order By: Relevance
“… It is non-toxic and blood-compatible. [ 100 ] P/ZnO hybrid NCs Donepezil The nanocomposite had more drug adsorption (273.91 mg/g) than the parent gel (35.55 mg/g). In vitro drug release studies revealed that the NCs increased drug desorption by up to 88% over a 5-day period when compared to the parent gel (46% over a 120-h period).…”
Section: Pectin and Its Modified Ncs For Drug Delivery Applicationsmentioning
confidence: 99%
“… It is non-toxic and blood-compatible. [ 100 ] P/ZnO hybrid NCs Donepezil The nanocomposite had more drug adsorption (273.91 mg/g) than the parent gel (35.55 mg/g). In vitro drug release studies revealed that the NCs increased drug desorption by up to 88% over a 5-day period when compared to the parent gel (46% over a 120-h period).…”
Section: Pectin and Its Modified Ncs For Drug Delivery Applicationsmentioning
confidence: 99%
“…In attending to the needs of the rising population of the world, rapid industrialization is taking place that is leading to the environmental pollution [ 1 , 2 , 3 , 4 ]. One of the major sources of pollution is wastewater released mainly from chemical industries; this industrial wastewater contains high concentrations of organic waste and heavy metal ions; by their nature, these are highly poisonous and carcinogenic, causing negative impact on sustainability of water resources [ 5 , 6 , 7 ]. Recently, environmental remediation technologies such as adsorption, chemical oxidation, incineration, and biological oxidation have been used in all types of organic and toxic wastewater treatment and also have various advantages in solar energy utilization, sensing, environmental treatment, and biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…There are many reports of the successful application of layer-by-layer nanocoatings on the design of antimicrobial surfaces. Polyelectrolyte membranes, a type of material in high demand in health and environmental sectors, can play an essential role in this purpose [ 20 , 21 , 22 , 23 ].…”
Section: Introduction (Semi-review)mentioning
confidence: 99%